SOSIALISASI DAN PENDAMPINGAN PENCEGAHAN PENYEBARAN COVID-19 DI PERUM TANGGAP COVID (PTC) AMERTA RESIDENCE RT 08/RW 05 DESA SAPTORENGGO - Nuril Hidayati; Trio Ageng Prayitno; Riyanto Riyanto (JPM PAMBUDI, 2020)
Saptorenggo Village is declared as a Covid-19 red zone. However, the villagers, especially the residents of Perum Amerta Residence continue to engage in outdoor activities even some of them still work out of town. This behavior is a source of major problem in the distribution of Covid-19 at the Amerta Residence housing estate. A mutual agreement between the service team and the head of RT 08 and residents of the Amerta Residence housing estate to overcome the problem is needed so that the socialization and assistance in preventing the spread of Covid-19 can be performed. This type of activity is community service at the Amerta Residence RT 08 housing estate from March to June 2020. The procedure for community service activities consists of four stages including socialization through deliberations, the formation of the Perum Tanggap Covid (PTC) team, periodic disinfectant spraying assistance, and evaluation of community service activities. The results of this community service show that the community service team has succeeded in carrying out community service activities base on the planned targets. In addition, residents of Amerta Residence housing estate can follow all the service activities that have been designed by the service team